ANALISIS PENGARUH VARIABEL EKONOMI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN HALMAHERA TIMUR - Hilman ., Duko; Paulus A. Pangemanan; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2018)
This study aims to (1) determine the influence of labor, investment, inflation rate, and change of head of region to economic growth in East Halmahera Regency at North Maluku Province, during the period 2004-2014, (2) and calculate the economic growth rate until 2019 based on the dominant economic sector. The type of research using library research method using PDRB data, East Halmahera Regency during 2004-2014 period published by Central Statistics Agency which calculated based on constant price in 2000. Model estimation results are calculated with the help of SPSS applications. The results showed the three variables (economic growth, labor, investment, and inflation) partially influence significantly to the variable of economic growth. While, the variable of Pilkada's existence was not gave a significant effect on economic growth. The average rate of economic growth generated by the government and society in this regency is cumulatively reaching 8.18% per year.